An evaluation of the 'Switch‐on Reading' literacy catch‐up programme. (8th August 2014) - Gorard, Stephen; Siddiqui, Nadia; See, Beng Huat
<x xml:space="preserve">Abstract</x> This paper is based on one of the first completed studies funded by the Educational Endowment Foundation (EEF). EEF was set up in response to repeated demands for clearer evidence on school improvement. The paper presents the results of an intensive 10‐week literacy intervention called Switch‐on Reading. This was trialled in England as part of a government initiative to assist children below Level 4 literacy while at age 10 to catch up with their peers on transfer to secondary school. Switch‐on took place in 19 Nottinghamshire schools, with 314 year 7 pupils individually randomised to treatment in the first or second term of school year 2012/13. This is the largest trial so far conducted of this kind of 10‐week reading intervention. It was delivered on a one‐to‐one basis by trained school staff, mostly teaching assistants. The independent evaluation was based on pre and post administration of the New Group Reading Test, and on observations and interviews in schools. The overall result was an effect size of +0.24, based on the pooled standard deviation of the post‐test score (and the gain score) for both groups, meaning that the programme made a noticeable positive impact. This effect can be envisaged as suggesting that on average a pupil receiving the intervention would make approximately three additional months' progress over the course of a year compared with similar pupils who did not, at a cost of around £600. The evaluation identified positive results for all groups of pupils (defined by sex, first language, ethnicity, special educational needs, free school meal eligibility and measured attainment at the outset). The trial also illustrates a key role for teaching assistants and shows the feasibility of the EEF research programme.